Environmental Law And Regional Autonomy: Opportunities And Challenges In Managing Natural Resources - Sukirno Sukirno (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Decentralization and regional autonomy are pivotal in reshaping Indonesia's governance, particularly in managing natural resources. In environmental law, regional autonomy empowers local governments to take a more active role in protecting and managing the environment by local characteristics. However, the exercise of this authority is not without its hurdles, including regulatory disharmony between the central and regional governments, institutional capacity constraints, and underdeveloped oversight and public participation systems. This study examines the opportunities and challenges that arise when implementing environmental law within the framework of regional autonomy, with a specific focus on regulatory, institutional, and participatory aspects. The methods employed are a legal-normative and empirical approach involving an analysis of legislation, scientific literature, and case studies in several natural resource-producing regions. The study findings underscore that decentralization paves the way for reinforcing regional roles. However, this potential has not been fully harnessed due to the lack of policy synchronization and implementation capacity. The strategic role of regions in environmental protection continues to be impeded by the dominance of central authority, particularly in the mining and forestry sectors. Therefore, it is recommended that regulations be harmonized across levels of government, human resource, and institutional capacity in regions be bolstered, and community participation mechanisms in environmental decision-making processes be fortified. With this strategy, environmental law can emerge as a tool for ecological justice firmly rooted in local autonomy, fostering inclusivity through community participation.